Modern Paradigm of Rural Public Management: The Case of Ukraine - KALACHEVSKA, LARYSA I.; SLAVKOVA, OLENA P.; LUKASH, SVITLANA M.; BRYCHKO, ALINA M. (The journal of contemporary issues in business and government, 2020)
Effective public management is a guarantee for ensuring stable long-term rural development in Ukraine. The aim of this research is to develop a set of directions for improving the efficiency of public management of Ukrainian rural areas based on the assessment of their development, identification of problems of rural management and learning from the experience of the European Union. The following methods are used: quantitative analysis of statistical data on the socio-economic development of Ukrainian rural areas and agriculture in Ukraine for the time period of ten years using one-dimensional statistical methods (UT) based on dependent, representative, and probabilistic sampling; comparative assessment of public management and state administration by means of literary review; “goal tree”, SMART-technology and analytical form of Boolean algebra logical function used for forming a goal hierarchy by every subject of rural public management in Ukraine, as well as achieving the common general goal of PM in Ukrainian rural areas; formation of an integral indicator for assessing the quality of rural public management within the framework of the developed assessment methodology; quantitative identification of consumers’ key requirements regarding services of state and municipal government institutions in the framework of effective rural public management based on the use of panel data. This article reveals trends and problems of rural public management in Ukraine and concludes that it is necessary to improve the efficiency of such management, for which a set of optimization measures is being developed.